PERANCANGAN MAGNETIC NEAR FIELD PROBE MURAH MENGGUNAKAN PCB FR-4 DUA LAPIS - Novemi Srihartini Almus; Noptin Harpawi (ABEC Indonesia, 2021)
The high density of circuit integration results in complex electromagnetic interference (EMI). measurement mapping Near-field is an effective method for locating radiation sources, redesigning circuits, and improving the EMC performance of electronic systems. Therefore, the probe is a key component inmeasurements near-field. The near-field probe is anprobe appropriatefor this measurement because it is capable of measuring radio frequency (RF) magnetic field levels from small sources. In this research,is designed and implemented magnetic The near-field probe is made from a two-layer FR-4 PCB with a relative permittivity value of 4.6 and a thickness of 1.6 mm. FR-4 PCB material was chosen because it is cheaper so it can save development costs. The probe can be used in range thefrequency 10 KHz to 1 GHz. The probe is designed based on a loop with atransmission microstripline. Thereturn loss minimumis -23.17 dB at a frequency of 935 MHz with a VSWR of 1.149. To measure the power level using the DUT EM Demo Board with a measurement distance of 1 cm to 6 cm. The greater the measurement distance, the smaller the power level value and vice versa.